The Use of Molasses in Producing Bioethanol Catalyzed by Candida tropicalis (Isolated from Cocos nucifera. L) Immobilized MnFe2O4 Coated-Chitosan - Kasmiarti, Getari; Hermansyah, Hermansyah; Novia, Novia; Hariani, Poedji Loekitowati (Universitas Jenderal Soedirman, 2024)
Bioethanol is a sustainable fuel product to be an alternative energy source. Therefore, the study aims to observe and analyze the effect of MnFe2O4 coated-chitosan in increasing bioethanol production. This bioethanol was produced from molasses with a high total sugar content of up to 50% with Candida tropicalis as the microorganism. Fermentation is divided into two parts, namely using free C. tropicalis and C. tropicalis immobilized MnFe2O4 coated-chitosan. There was electrostatic interaction between MnFe2O4 and chitosan in 578 cm-1 and 659 cm-1 of FTIR, cubic spinel pattern in XRD, and SEM surface image of C. tropicalis immobilized MnFe2O4 coated-chitosan interaction. These characterization results show very good properties as a biocatalyst. The highest concentration was produced by fermentation using C. tropicalis immobilized MnFe2O4 coated-chitosan about 4.35% with residual sugar of 8.46 g/L. In summary C. tropicalis immobilized MnFe2O4 coated-chitosan have the potential to improve bioethanol products.